2006
DOI: 10.1021/om060863m
|View full text |Cite
|
Sign up to set email alerts
|

N−H versus C−H Activation of a Pyrrole Imine at {Cp*Ir}:  A Computational and Experimental Study

Abstract: Reaction of a pyrrole imine with [IrCl 2 Cp*] 2 /NaOAc leads to N-H actiVation in preference to C-H actiVation at the pyrrole; howeVer, with the N-methylated ligand C-H actiVation occurs. Density functional calculations show that N-H bond actiVation is both kinetically and thermodynamically preferred to C-H actiVation. Both reactions occur with relatiVely low energy barriers by an electrophilic agostic interaction with the metal with simultaneous intramolecular hydrogen bonding with acetate leading to deproton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 19 publications
4
63
0
Order By: Relevance
“…Although the computed barriers of >40 kcal mol −1 are rather high for room temperature processes, the different transition state geometries show some interesting features: C(sp 3 )-H activation is dominated by interaction with the base (TS53: C · · · H = 1.81 Å, O · · · H = 1.04 Å, Ir · · · H = 2.77 Å), while the metal plays a more prominent role in the C(sp 2 )-H activation (TS54: C · · · H = 1.38 Å, O · · · H = 2.89 Å, Ir · · · H = 1.66 Å). This is consistent with the AMLA concept in which the complementary involvement of base and metal combines to accommodate the activation of a wide range of different C-H bonds[59].…”
supporting
confidence: 88%
“…Although the computed barriers of >40 kcal mol −1 are rather high for room temperature processes, the different transition state geometries show some interesting features: C(sp 3 )-H activation is dominated by interaction with the base (TS53: C · · · H = 1.81 Å, O · · · H = 1.04 Å, Ir · · · H = 2.77 Å), while the metal plays a more prominent role in the C(sp 2 )-H activation (TS54: C · · · H = 1.38 Å, O · · · H = 2.89 Å, Ir · · · H = 1.66 Å). This is consistent with the AMLA concept in which the complementary involvement of base and metal combines to accommodate the activation of a wide range of different C-H bonds[59].…”
supporting
confidence: 88%
“…This is consistent with the AMLA concept, with complementary involvement of base and metal combining to accommodate the activation of a wide range of different C-H bonds [27].…”
Section: C(sp 3 )-H Activationsupporting
confidence: 87%
“…26 Although it can be challenging to distinguish between different C−H activation mechanisms experimentally, much insight has already been gained using theoretical methods. 2b This includes the computational studies of the mechanism of cyclometalation in aromatic C−H activation by Davies and Macgregor 27,28 and also studies on the mechanism of palladium-catalyzed intramolecular arylation by Maseras and Echavarren. 29 On the basis of the results from the Hammett study, the C− H activation step should involve a proton abstraction.…”
Section: ■ Computational Studymentioning
confidence: 99%
“…That an acetate anion can act as an internal base to facilitate the cleavage of a C−H bond has been reported previously with an iridium catalyst. 28,30 For allylic C−H oxidation, White and coworkers have suggested that a carboxylate counterion on palladium is needed to effect C−H cleavage. 31 A carboxylate anion also plays a key role in the C−H activation step of the proposed Pd(II)/Pd(IV) catalytic cycle for an allylic C−H acetoxylation 32 or as a base in a recently published allylic acyloxylation.…”
Section: ■ Computational Studymentioning
confidence: 99%